Peculiarities of vegetative regulation of heart activity and diurnal profile of blood pressure in patients with acute myocardial infarction, complicated by left ventricle aneurysm - S. M. Kyselov (Zaporožskij Medicinskij Žurnal)
In patients with myocardial infarction indexes of vegetative regulation of heart activity and diurnal blood pressure profile are connected with complicated trend of the disease.